Prediction of Communicative Disorders Linked to Autistic Spectrum Disorder Based on Early Psychomotor Analysis - Darío Rincón-Rufo; Violeta Vera-Pérez; Alicia Cuesta-Gómez; María Carratalá-Tejada (MDPI AG, 2022)
This systematic review evaluated psychomotor differences between children with and without siblings who have autism spectrum disorder (ASD), as well as the most reliable psychomotor skills that can help predict ASD and its associated language disorders. Literature from 2005 to 2020 was searched using the following databases: PubMed, Trip Medical Database, Cochrane, Web of Science, Science Direct, and Brain. A total 11 papers were included. Fine motor skills and joint attention displayed reliable results in order to predict ASD and its associated language disorders. The period between the first and the second year of life was considered the most appropriate one for the assessment of psychomotor skills. The best period to predict language disorders and ASD diagnosis is around 36 months old.